PENGARUH PEMBERIAN TABLET FE TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI DI SMPN 17 WILAYAH KERJA PUSKESMAS PIR II BAJUBANG MUARO JAMBI TAHUN 2023 - Dewi Riastawaty; Imelda - (Universitas Prima Indonesia, 2023)
Anemia is Wrong One problem health all over world especially country an estimated 30 % of the population world suffering from anemia. Anemia is Wrong One problem nutrition , where rate hemoglobin (HB) in blood more low. Addition of Tablets Blood (TTD) is Wrong One that effort done For prevent And treat nutritional anemia iron on teenager daughter. Study This aim For know influence administration of Fe tablets to hemoglobin level on teenager daughter at SMPN 17 Region Work PIR II Bajubang Health Center Muaro Jambi in 2023, Research is study pre experiment one group pre test post test. Population as many as 22 people and sample totaling 22 people. Technique taking sample with method total sampling. Study This held on month January 2023. Data analysis used is Analysis Univarit And Bivariate use test T-test . Results study show that the average rate Hb teenager daughter of SMPN 17 Work Area PIR II Bajubang Health Center Muaro Jambi is 10,3 g /dl. Rate average Hb teenager daughter of SMPN 17 Work Area PIR II Bajubang Health Center Muaro Jambi is 11,11 g /dl. Based on results statistical test obtained mark p-value 0.000 (p<0 .05 ) means there is influence administration of Fe tablets to hemoglobin level on teenager daughter at SMPN 17 Work Area PIR II Bajubang Health Center Muaro Jambi in 2023. Suggestions that are expected to continue increase And support health programs teenagers, especially with problem administration of Fe tablets to hemoglobin level on teenager daughter.